Design of Omron PLC Based Automatic Car Wash Prototype - Anggoro, Rois Aditya Yoga; Puriyanto, Riky Dwi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Increasing automotive production indirectly greatly affects the progress of an increasingly modern era. Indirectly, production in factories will increase to meet the needs and desires of transportation consumers. Therefore, the use of PLC in the industrial sector as production plays an important role in helping humans to do heavy work. The growing demand for increased mobility needs will indirectly require owners to take care to maintain cleanliness in mobility transportation. Therefore, we need a system that can control automatic car washing. This automatic car wash system uses PLC CJ1M with a prototype design of 24cm long, 15cm wide and 15cm high and uses an infrared sensor which is used to read the presence of the car and a pg28 dc motor which is used as the main driver. The programming language used is the ladder language in CX-Programmer. Where this ladder language is used to control several processes, namely, watering, soaping, scrubbing, rinsing water and the drying process. From this research, the researcher obtained the results that the time obtained from manual and automatic calculations to run a washing process by giving a set value of 5 on the counter will give the difference in time obtained, namely watering 1.54 seconds, sprinkling soap water 3.01 seconds, rubbing 3.13 seconds, 3.09 seconds of water rinsing and the same time for the drying process. From the use of the infrared analog sensor used, it successfully reads the presence of the car in front of it and the design of this prototype runs with a predetermined process.